TITIK TEMU ISLAM DAN DEMOKRASI : ANALISIS SISTEM PEMILIHAN UMUM PRESIDEN DI TURKI DAN INDONESIA - Al djufri, Helmy; Alfaridah, Dini Inasyah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2023)
Democracy is a system that exists in various countries with a government where supreme power lies in the hands of the people. However, in reality the implementation of democracy is difficult to implement ideally in accordance with the values contained in democracy itself, and how democracy is implemented in Islamic democracy, especially if the election systems between Turkey and Indonesia are clearly different or have similarities between the two. One thing that often happens regarding the implementation of democratic government is presidential elections, so that we can compare Islam and democracy in these two countries. This research uses normative juridical research methods obtained from library data and statutory regulations. The results of this research show that firstly, the Presidential General Election in Indonesia and Turkey are clearly stated in the Constitution, both the Constitution of the Republic of Turkey and the 1945 Constitution in Indonesia, as for the mechanism for the direct Presidential General Election System, it is regulated in article 2 of Law Number 7 2017 regarding the Presidential General Election. Meanwhile. The two similarities are related to the system for holding the Presidential General Election, namely using a direct election system and regarding the comparison of the Presidential Elections of the Republic of Indonesia and Turkey, there are many Similarities were found, such as the presidential election system in both countries using a direct election system, presidential candidates having to be nominated by a party, the party system using a multiparty system, the existence of a party threshold for nominating the president and office of President in Indonesia an Turkey which is 5 (five) years for a period and can be nominate for two more periods. Meanwhile, the difference between the general elections of the Republic of Indonesia and Turkey is that there is a minimum age limit for the president and a threshold percentage for the party. Demokrasi ialah suatu sistem yang dimiliki di berbagai negara dengan pemerintahan yang kekuasaan tertinggi terletak di tangan rakyat. Namun kenyataannya penyelenggaraan demokrasi sulit untuk diimplementasikan secara ideal sesuai dengan nilai-nilai yang dikandung dalam demokrasi itu sendiri, dan bagaimana demokrasi yang diterapkan dalam demokrasi Islam, apalagi jika sistem Pemilu antara negara Turki dan Indonesia jelas berbeda atau ada persamaan dari duanya. Salah satu yang sering banyak terjadi mengenai penyelenggaraan pemerintahan demokrasi ialah seperti pemilihan umum presiden, sehingga kita bisa membandingkan Islam dan demokrasi di dua negara tersebut. Penelitian ini menggunakan metode penelitian secara yuridis normatif yang diperoleh dari data kepustakaan, peraturan perundang-undangan. Hasil penelitian ini menunjukkan bahwa Pertama, Pemilihan Umum Presiden di Indonesia dengan di Turki telah jelas tertuang dalam Konstitusinya baik itu Konstitusi Republik Turki dan di Indonesia UUD 1945, adapun mekanisme Sistem Pemilihan Umum Presiden secara langsung, diatur di dalam pasal 2 Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum Presiden, Kedua kesamaan terkait dengan sistem penyelenggaraan Pemilihan Umum Presiden yaitu menggunakan sistem pemilihan langsung dan mengenai perbandingan Pemilihan Umum Presiden Republik Indonesia dan Turki banyak ditemukan persamaan, seperti sistem pemilihan umum presiden kedua negara menggunakan sistem pemilihan langsung, calon presiden harus diusung partai, sistem kepartaian yang menggunakan sistem multipartai, adanya ambang batas partai untuk mengusung presiden dan masa jabatan Presiden selama 5 (tujuh) tahun dan dapat mencalonkan kembali maksimal 2 (dua) kali periode. Sedangkan yang menjadi perbedaan pemilihan umum Republik Indonesia dan Turki yaitu adanya batas minimal usia presiden dan persentase ambang batas partai.